2012
DOI: 10.1002/art.34346
|View full text |Cite
|
Sign up to set email alerts
|

Association of anticytomegalovirus seropositivity with more severe joint destruction and more frequent joint surgery in rheumatoid arthritis

Abstract: Objective. Expansion of autoreactive CD4؉ CD28null T cells is associated with extraarticular disease manifestations, including rheumatoid vasculitis, and it has recently been demonstrated that expansion of these T cells is associated with anticytomegalovirus (anti-CMV) seropositivity. This study was undertaken to investigate a possible link between latent CMV infection and rheumatoid arthritis (RA).Methods. In a retrospective analysis, anti-CMV antibodies and clinical, serologic, and radiologic parameters of j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
2
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 41 publications
6
38
2
2
Order By: Relevance
“…Therefore, CMV infection may result in increased risk of autoantibody production, which could precede the onset of autoimmune disease. A recent study has reported that in CMV-infected RA patients joint destruction is more severe than in CMV-uninfected RA [64]. Chronic persistent pathogens, like CMV, are frequently reactivated in human autoimmune disease and can target the site of autoimmune inflammation [65].…”
Section: Immunosenescence Gender and Rheumatoid Arthritismentioning
confidence: 99%
“…Therefore, CMV infection may result in increased risk of autoantibody production, which could precede the onset of autoimmune disease. A recent study has reported that in CMV-infected RA patients joint destruction is more severe than in CMV-uninfected RA [64]. Chronic persistent pathogens, like CMV, are frequently reactivated in human autoimmune disease and can target the site of autoimmune inflammation [65].…”
Section: Immunosenescence Gender and Rheumatoid Arthritismentioning
confidence: 99%
“…Rheumatoid arthritis Latent CMV infection influences the clinical course and outcome of rheumatoid arthritis (RA) (Davis et al 2012;Pierer et al 2012), and CMV has been associated with more severe joint disease in patients with RA (Rothe et al 2016). Specific immunopathogenic mechanisms through which CMV could contribute to aggravation of joint damage in RA patients include the expansion of CMV-specific CD4+ CD28− (Pawlik et al 2003) and CD8+CD28− (Rothe et al 2016) T cells, which directly contribute to tissue lesions.…”
Section: And Autoimmune Diseasesmentioning
confidence: 99%
“…Only few studies were found that have determined HCMV seroprevalence in RA patients: whereas higher HCMV coincidence with RA was found in one report [91], the two others did not observe this [83, 100]. All studies were carried out in Europe.…”
Section: Prevalence Of Hcmv Igg In Patients With Autoimmune Diseasementioning
confidence: 99%